Pengaruh Latihan Peningkatan Ketepatan Passing Bawah Dengan Metode Drill Pemberian Smash Pada Atlet Bolavoli Putra Universitas Negeri Malang - Nanda Maulana P; Slamet Raharjo; Olivia Andiana; Ahmad Abdullah (Gerak: Journal of Physical Education, Sports, and Health, 2022)
Accuracy improvement training is a training technique that can increase the accuracy of passing under the volleyball, at this time the male volleyball athletes of the State University of Malang will face the championship and need to do special training, including on the lower passing technique. This study aims to be able to see the effect of training to increase the accuracy of lower passing with the drill method of giving smashes to male volleyball athletes, State University of Malang. This study used experimental research using a one group pretest-posttest design. The sample in the study was 20 athletes. This exercise is carried out in a period of 6 weeks with three days a week. The lower passing accuracy test is carried out twice, namely before the treatment (pre-test) and after the treatment (post-test). The results of the paired t test obtained a significance value of 0.000 < 0.05, this means that there is a change and shows that H0 is rejected and H1 or hypothesis is accepted. Based on the results of the study, it can be concluded that the exercise can affect the accuracy of lower passing in male volleyball athletes, State University of Malan